Microbial Contamination of Infant Milk Formula in Local Markets - Baghdad Science Journal (مجلة بغداد للعلوم, 2016)
This study is conducted to identify the microbial content of some types of infant milk formula available in the local markets of the city of Baghdad and their conformity microbial limits sited by the Iraqi standard. Seventy samples were collected from trademarks of imported infant milk formula included of five samples of infant milk formula No (1) and five samples of follow-up formula No (2). These samples were collected randomly from shops in the local markets of Baghdad city on both sides of Karkh and Rusafa included the following kinds: Dialac 1, Dialac 2 ,Celia 1, Celia 2 ,Biomil 1, Biomil 2 , Nactalia 1, Nactalia 2, Novalac 1 , Novalac 2 , Similac 1 , imilac 2 , Guigos 1, Guigos 2. Some microbial tests were done which included estimating the number of Total Plate Count bacteria, Coliform bacteria, Salmonella bacteria, Staphylococcus bacteria and Molds,Yeasts . The results show there is no any type of Coliform and Salmonella bacteria in infant milk; While high number of total plate count bacteria, Staphylococcus bacteria,Yeasts and Molds are showed in all kinds of formula, therefore do not exceed the microbiological limits of Iraqi standards(IQS) for good quality infant milk powder, with except the trademark Dialac1, Dialac 2 .